Regional anaesthesia and patients with abnormalities of coagulation. (1st August 2013) - ,; Harrop‐Griffiths, W.; Cook, T.; Gill, H.; Hill, D.; Ingram, M.; Makris, M.; Malhotra, S.; Nicholls, B.; Popat, M.; Swales, H.; Wood, P.
Summary Concise guidelines are presented that relate abnormalities of coagulation, whether the result of the administration of drugs or that of pathological processes, to the consequent haemorrhagic risks associated with neuraxial and peripheral nerve blocks. The advice presented is based on published guidelines and on the known properties of anticoagulant drugs. Four separate Tables address risks associated with anticoagulant drugs, neuraxial and peripheral nerve blocks, obstetric anaesthesia and special circumstances such as trauma, sepsis and massive transfusion.